2018
DOI: 10.1093/rheumatology/key174
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induces protein carbamylation in fibroblast-like synoviocytes from patients with rheumatoid arthritis

Abstract: These data indicate that autophagy is able to induce in vitro carbamylation processes, and in vivo appears to be related to an increase in carbamylation during RA. These observations introduce a new pathogenetic mechanism of disease, which could contribute to more accurate monitoring of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Autophagy actively participates in protein citrullination and carbamylation by substrates for the formation of autoantibodies [9, 10]. In fact, stimuli that induce autophagy were able to activate PAD4 enzyme in FLS from RA patients [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy actively participates in protein citrullination and carbamylation by substrates for the formation of autoantibodies [9, 10]. In fact, stimuli that induce autophagy were able to activate PAD4 enzyme in FLS from RA patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, ex vivo analysis in monocytes from early-naïve RA patients revealed an interesting direct correlation between autophagy levels and anti-cyclic citrullinated peptide (anti-CCP) titer. Recently, the same experimental condition was used to demonstrate that also carbamylation process was related to autophagy activation [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that autophagy may be involved in the carbamylation of FLS proteins, a non-enzymatic posttranslational modification mechanism, which results in their accumulation and subsequent participation in the pathogenesis of RA. However, the specific mechanism underlying this phenomenon is not yet clear (119).…”
Section: Autophagy Increases Auto-antigen Presentation By Antigen-presenting Cellsmentioning
confidence: 99%
“…Smoking may also induce carbamylation [ 232 ], and mononuclear cells of treatment-naïve RA patients show a correlation between autophagy and the level of carbamylation [ 233 ]. The carbamylated form of hemoglobin and low-density lipoprotein (LDL), detectable by laboratory tests, is correlated with acute or chronic renal failure and atherosclerosis, respectively [ 234 , 235 , 236 , 237 , 238 ].…”
Section: Carbamylation In Ramentioning
confidence: 99%